PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. WANA JINGGA TIMUR KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Bismi Eka Putri; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at PT. Wana Jingga Timur Cerenti District Kuantan Singingi Regency. The purpose of this study was to determine the effect of work discipline and work environment on employee performance at PT. WanaJinggaTimurCerenti District KuantanSingingi Regency. Work discipline (X1), work environment (X2) and employee performance (Y).             The research method used is quantitative descriptive analysis obtained from the result of the questionnaire measured by a Likert scale which is then processed by the SPSS program. The sample of this study was 51 respondents from the population which was calculated using the Slovin formula. This study used the method of simple linear regression analysis and multiple linear regression analysis.The result showed that work discipline had an effect on employee performance with t count > t table (6,597 > 2,821) and significance (0,000 < 0,05). The work environment affected employee performance with t count > t table ( 7,056 > 3,298) and significance (0,000 < 0,05). Work discipline and work environment have an effect on employee performance with F arithmetic value > F table (30,555 > 3,19) and significance (0,000 < 0,05) it can be concluded that work discipline and work environment have a positive and significant influence on employee performance at PT. Wana Jingga Timur Cerenti District Kuantan Singingi Regency.Keywords: Work Discipline, Work Environment, Employee Performance